2020
DOI: 10.15298/invertzool.17.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Macroparasites of epipelagic and eurybathic fishes in the north-western Pacific

Abstract: A total of 25 parasitic species were found to infect 23 species of teleost and two species of cartilaginous fish in the north-western Pacific. Known generalists, anisakid and raphidascaridid juveniles (Nematoda), plerocercoids of Nybelinia surmenicola (Cestoda), and acanthocephalan Echinorhynchus gadi (Acanthocephala) were prevalent; however, plerocercoids of Pelichnibothrium speciosum were the most common parasites of epipelagic and eurybathic fish, infecting 16 out of 23 examined teleost species. Digenean in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 6 publications
4
8
1
Order By: Relevance
“…Tables 1, 2). The absence of Brachyphallus crenatus (Rudolphi, 1802) in the guts of chum and pink salmon in our previous parasitological study in the open water of north-western Pacific (Gordeev, Sokolov, 2020b) was strikingly different from the data collected by Mamaev et al (1959), who showed a heavy infection with this parasite (up to 750 worms per fish). In our research B. crenatus was present in the stomachs of both salmon species, but the value of infection never exceeded five worms per fish further investigation.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Tables 1, 2). The absence of Brachyphallus crenatus (Rudolphi, 1802) in the guts of chum and pink salmon in our previous parasitological study in the open water of north-western Pacific (Gordeev, Sokolov, 2020b) was strikingly different from the data collected by Mamaev et al (1959), who showed a heavy infection with this parasite (up to 750 worms per fish). In our research B. crenatus was present in the stomachs of both salmon species, but the value of infection never exceeded five worms per fish further investigation.…”
Section: Discussioncontrasting
confidence: 88%
“…Tables 1, 2). This observation indirectly confirms our earlier ideas about the presence of waves of infection with B. crenatus (Gordeev, Sokolov, 2020b). We dissected only four individuals of O. keta from the Bering Sea, which is not enough for any conclusions.…”
Section: Methodssupporting
confidence: 88%
“…The F abs of the Fedorov's lumpsucker in our study was significantly lower than that reported for other species of Cyclopteridae. For example, in another study, fecundity of lumpfish ranged from 50,000 to 159,000 eggs (Gregory and Daborn, 1982). The values of F abs of Atlantic spiny lumpsucker and smooth lumpsucker have been reported to be more than 1000 eggs (Dolgov 2 ; Hutchings 3 ) and between 24,240 and 63,756 eggs (Zhukova et al, 2018), respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Sebastes ruberrimus exhibits very low infection rates of P. decipiens, and except for one highly infected individual, low infection rates by A. simplex. It may be that parasite abundance or diversity in fish may be higher at shallower depths [30]. The pelagic-feeding rockfish can be divided into two groups based on the average depth they occupy.…”
Section: Discussionmentioning
confidence: 99%